Análise do /s/ pós-vocálico no português brasileiro: coda ou onset com núcleo foneticamente vazio? - Pedrosa, Juliene Lopes Ribeiro (2009)
There has been a lot of discussion about the post-vocalic /s/ and its variable behavior in Brazilian Portugueses, as in Brescancini Brescancini (2002); Callou, Leite, Moraes (2002); Hora (2003); Ribeiro (2006); among others. All of them agree that /s/ occupies the coda position, alternating alveolar (ca[s]ca, me[z]mo, feli[s]), palatal (po[]te, de[]de, mai[]) and glotal (de[h]de, me[h]mo, mai[h]) realizations, and also deletion (me[]mo, mai[]), when the syllabic pattern turns into the less marked one (CV). Although this conception is widespread within the phonological theory, we believe that the particular status the coronal fricative possesses in relation to liquids and nasals (those licensed to occupy the coda position in Brazilian Portuguese) is a fact that deserves to be observed more carefully and one that can lead to another way of analysis. According to Harris & Gussmann (1998) and Ewen & Hulst (2001), some syllables can be formed by onset with a phonetically non-filled nucleus. Accordingly, these syllables satisfy the less marked pattern (CV) in underlying representation, but they do not show, in some cases, the phonetic representation in the surface. The fricatives would be prone to sustain the syllable weigh, since they have more frequency in duration in their production, and as such they do not need, in theory, the phonetic realization of their nuclei. These arguments make us, therefore, propose another classification of the post-vocalic /s/, considering it onset of a phonetically empty nucleus, that, in some dialects, is realized in final position ([fajzi], [majzi]). Therefore, our aim is to analyze the post-vocalic /s/ in Brazilian Portuguese, with the variationist results from Brescancini (2002); Callou, Leite, Moraes (2002); Hora (2003) and Ribeiro (2006), in order to highlight its variable pattern and to propose a ranking for Brazilian Portuguese, using, for such, the Optimality Theory (OT) in Coetzee‟s perspective. In this proposal, the evaluator (EVAL) realizes a harmonic ranking for the set of candidates, in a way that the losers are also ranked, that is, both the constraints and the candidates are ranked. In this way, it is possible to work with non-categorical phenomena, as such related to variation, and to produce a proficuous link between the Sociolinguistic Research and Optimality Theory.